2012
DOI: 10.5007/1980-0037.2012v14n2p212
|View full text |Cite
|
Sign up to set email alerts
|

Confiabilidade de medidas de arquitetura muscular do tríceps sural por ultrassonografia de imagem. DOI: 10.5007/1980-0037.2012v14n2p212

Abstract: Resumo -Há, atualmente, na literatura, poucas pesquisas de confiabilidade e validação da quantificação de parâmetros de arquitetura muscular por ultrassonografia (US), relatando informações importantes como o erro típico da medida (ETM) e o coeficiente de correlação intraclasse (ICC). O objetivo do estudo foi aplicar a técnica de US para quantificar as medidas de comprimento da fibra (CF) e ângulo de penação (AP) dos músculos gastrocnêmios e determinar a confiabilidade e a reprodutibilidade dessas medidas. Dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(48 reference statements)
0
1
0
1
Order By: Relevance
“…The absence of a change in PA post-eccentric training might be due to measurement errors in US image analysis (Baroni et al, 2013b). While eccentric training and conventional resistance training seem to increase plantar flexor PA by around 1.2–4.0° (Morse et al, 2007; Duclay et al, 2009; Vieillevoye et al, 2010; Sanz-Lopez et al, 2016), ultrasonographic analyses have shown a TE of 0.15–3.7 (de Boer et al, 2008; Padhiar et al, 2008; Martins et al, 2012; McMahon et al, 2016). Reported PA adaptive responses to strength training are close to the measurement error in US analysis, which could explain results from studies that found an increase in muscle hypertrophy without concomitant changes in PA (Reeves et al, 2009; Raj et al, 2012; Baroni et al, 2013b; Fouré et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a change in PA post-eccentric training might be due to measurement errors in US image analysis (Baroni et al, 2013b). While eccentric training and conventional resistance training seem to increase plantar flexor PA by around 1.2–4.0° (Morse et al, 2007; Duclay et al, 2009; Vieillevoye et al, 2010; Sanz-Lopez et al, 2016), ultrasonographic analyses have shown a TE of 0.15–3.7 (de Boer et al, 2008; Padhiar et al, 2008; Martins et al, 2012; McMahon et al, 2016). Reported PA adaptive responses to strength training are close to the measurement error in US analysis, which could explain results from studies that found an increase in muscle hypertrophy without concomitant changes in PA (Reeves et al, 2009; Raj et al, 2012; Baroni et al, 2013b; Fouré et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Además, las diferencias en la arquitectura muscular de los músculos extensores de la rodilla, cuando son comparados con los flexores plantares como el ángulo de penación de las fibras de los gastrocnemios y el largo del tendón de inserción en el calcáneo (Martins et al, 2012), que difieren mucho del músculo vasto lateral, lo que también pueden tener influencia en las diferencias con los resultados en ese estudio.…”
Section: Discussionunclassified